Properties of hot mix asphalt by replacing crumb rubber as fine aggregate - Noor Liyana, Ahazar (2017)
A lot of research has been conducted in finding other alternatives material in other to be used as modifier in asphalt mixes for the purpose of improving its characteristics. This research has been used crumb rubber in hot mix asphalt (HMA) as additive. Crumb rubber was identified to have a potential to becoming a modifier in HMA mixes due to the elastic behaviour exposed by the rubber particles especially in reducing rutting potential. The used of crumb rubber in this research is to replace fine aggregate by a percentage which is 1%, 2% and 3% of crumb rubber with the weight of aggregate. The size of crumb rubbers used in this research is 0.3 mm, with three difference percent of bitumen content (4%, 5% and 6%). The process used in this study is “dry process” which refers to the mix of crumb rubber with the aggregate prior to mixing it into the asphalt binder. The Marshall Stability Test method for asphalt mixture specimens was used in this research. All the specimens were prepared for evaluation of Marshall Properties which is to determine the flow, stability, bulk density, air void percentage and void in mineral aggregate. Based on the result, replaced the fine aggregate with crumb rubbers with percentage will affect the performance of Hot Mix Asphalt mixes (HMA mixes) significantly. By replacing with 1% of crumb rubber, it was identified that this percentage of crumb rubber is good enough to be chosen as the optimum for the crumb rubber replacement as fine aggregates in hot mix asphalt. Through this study also, the effect by replacing of crumb rubber as fine aggregate towards the air void had been found out. It can be concluded that with the increasing of crumb rubber percent, the air void also tends to increase. The result shown the percentage of crumb rubbers can be accepted regarding to the JKR Specification when replaced 1% of crumb rubbers.